Namestyle sebagai Pencitraan Visual Sebuah Film Animasi - Kartika, Rina; Riyadi, Tunjung (Bina Nusantara University, 2011)
Animation movie is one communication media. Image shape that could give reality impression to be interested message sender. History showed that special animation movie gives its own space and style to impress the audience. It is factual that audiences in any ages could acknowledge and enjoy animation moview. The fast-moving development of animation is along with the development of animation technology. Other factor is about promotion and story appeal of related movie. Promotion and story will give identity towards movie title. The movie title, which written suitably, has different appeal that will approach audience to watch the movie. In defining title and identity, there are different ways and designs, so the identity will last remain in the mind of the reader. The article describes namestyle and its relation with characters in some movies, especially Hollywood animation movie.